Its beautiful (Just observe it)

Algebra Level 3

{ 4 x 2 + 1 x = 5 y 2 + 1 y = 6 z 2 + 1 z x y z = x + y + z \begin{cases} 4\dfrac{\sqrt{x^{2} + 1}}{x} = 5\dfrac{\sqrt{y^{2} + 1}}{y}=6\dfrac{\sqrt{z^{2} + 1}}{z} \\ xyz = x + y + z\end{cases}

If x = a b , y = c d e , z = f g x = \dfrac{\sqrt{a}}{b} , y = c\dfrac{\sqrt{d}}{e} , z = f\sqrt{g} satisfy the above system of equations, then find ( a + b + + g ) (a + b + \ldots + g ) .

  • The expression is in simplest terms, meaning that all of the variables are positive integers, a , d , g a, d, g are square free and c , e c, e are coprime.


The answer is 41.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Sandeep Rathod
Nov 5, 2014

x = t a n a , y = t a n b , z = t a n c x = tana , y = tanb , z = tanc

x y z = x + y + z xyz = x + y+ z keeping the values it shows the property of a triangle

t a n a t a n b t a n c = t a n a + t a n b + t a n c tanatanbtanc = tana + tanb + tanc

t a n a = t a n b + t a n c 1 t a n b t a n c = t a n ( b + c ) - tana = \frac{tanb + tanc}{1- tanbtanc} = tan(b + c)

t a n ( k p i a ) = t a n ( b + c ) tan(kpi - a) = tan( b + c)

a + b + c = k p i a + b + c = kpi

4 t a n 2 a + 1 t a n a = . . . . . . 4\frac{\sqrt{ tan^{2}a + 1}}{tana} = ......

4 s i n a = 5 s i n b = 6 s i n c \frac{4}{sina} = \frac{5}{sinb} = \frac{6}{sinc}

for k = 1 there is a triangle whose sides are 4k , 5k and 6k

s = 15 2 s = \frac{15}{2}

t a n a 2 = ( s 5 k ) ( s 6 k ) s ( s 4 k ) = 1 7 tan\frac{a}{2} = \sqrt{\frac{(s - 5k)(s - 6k)}{s(s - 4k)}} = \sqrt{\frac{1}{7}}

x = t a n a = 2 t 1 t 2 = 7 3 x = tana = \frac{2t}{1 - t^{2}} = \frac{\sqrt{7}}{3} t = tana/2

similarly , y = 5 7 9 , z = 3 7 y =\frac{5\sqrt{7}}{9} , z = 3\sqrt{7}

Just amazing@Sandeep rathod

U Z - 6 years, 7 months ago

Log in to reply

I also did same thing! Really very nice question @megh choksi ! I enjoyed very much in solving it !

Deepanshu Gupta - 6 years, 7 months ago

Log in to reply

You are a genius i know

U Z - 6 years, 7 months ago

Log in to reply

@U Z Uhm, mind rewriting the first expression? I know that wasn't was it's suppossed to be.

Joeie Christian Santana - 6 years, 7 months ago

did the same...but at last ,without using the triangle,I just solved forming a equation...this problem was really a beauty

Souryajit Roy - 6 years, 6 months ago

x/√(x x+1)=sinX , y/√(y y+1)=sinY , z/√(z z+1)=sinZ. Now we have 4/sinX=5/sinY=6/sinZ,and this equations are similiar as sine law for triangle which sides are 4,5,6(4k,5k,6k exacly but we get least value,it's easier to calculte). So X,Y,Z are angles of tringle whisch sides are 4,5,6.From cosine law we found that cosX=(6 6+5 5-4 4)/(2 6 5)=3/4 so sinX=√(1-9/16)=√7/4.Same cosY=(6 6+4 4-5 5)/(2 4 6)=9/16,and sinY=√(1-81/256)=5√7/16,same way we found cosZ=(4 4+5 5-6 6)/(2 4 5)=1/8,and sinZ =3√7/8. now we replace that values and get x/√(x x+1)=√7/4,so 4x=√(7x x+7),when squared 16xx=7xx+7 , 9xx=7 , xx=7/9 , x=√7/3,similiar y/√(y y+1)=5√7/16, so 16y=√(175yy+175),when squared 256yy=175yy+175, which means yy=175/81,y=5√7/9, and same way z/√(z z+1)=3√7/8, meaning 8z=√(63zz+63),squared again 64zz=63zz+63,zz=63,z=3√7. We found that x=√7/3 , y=5√7/9 , z=3√7. x+y+z=√7(1/3+5/9+3)=√7(3+5+27)/9=35√7/9 xyz=(√7/3)(5√7/9) 3√7=5 7√7/9=35√7/9,so xyz=x+y+z and our x,z,y are solutions of this problem.It means a=7,b=3,c=5,d=7,e=9,f=3,g=7,so a+b+c+d+e+f+g=7+3+5+7+9+3+7=41.

Nikola Djuric - 6 years, 6 months ago

amazing I found it hard

Reece Brown - 5 years, 7 months ago
Nikola Djuric
Dec 2, 2014

x/√(x x+1)=sinX , y/√(y y+1)=sinY , z/√(z z+1)=sinZ. Now we have 4/sinX=5/sinY=6/sinZ,and this equations are similiar as sine law for triangle which sides are 4,5,6(4k,5k,6k exacly but we get least value,it's easier to calculte). So X,Y,Z are angles of tringle whisch sides are 4,5,6.From cosine law we found that cosX=(6 6+5 5-4 4)/(2 6 5)=3/4 so sinX=√(1-9/16)=√7/4.Same cosY=(6 6+4 4-5 5)/(2 4 6)=9/16,and sinY=√(1-81/256)=5√7/16,same way we found cosZ=(4 4+5 5-6 6)/(2 4 5)=1/8,and sinZ =3√7/8. now we replace that values and get x/√(x x+1)=√7/4,so 4x=√(7x x+7),when squared 16xx=7xx+7 , 9xx=7 , xx=7/9 , x=√7/3,similiar y/√(y y+1)=5√7/16, so 16y=√(175yy+175),when squared 256yy=175yy+175, which means yy=175/81,y=5√7/9, and same way z/√(z z+1)=3√7/8, meaning 8z=√(63zz+63),squared again 64zz=63zz+63,zz=63,z=3√7. We found that x=√7/3 , y=5√7/9 , z=3√7. x+y+z=√7(1/3+5/9+3)=√7(3+5+27)/9=35√7/9 xyz=(√7/3)(5√7/9) 3√7=5 7√7/9=35√7/9,so xyz=x+y+z and our x,z,y are solutions of this problem.It means a=7,b=3,c=5,d=7,e=9,f=3,g=7,so a+b+c+d+e+f+g=7+3+5+7+9+3+7=41.

can you please write in latex

U Z - 6 years, 6 months ago

Log in to reply

Where can I download Latex?

Nikola Djuric - 6 years, 6 months ago

Log in to reply

Can you edit your solution now , I think now you would have learned latex

U Z - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...